The Faithful and the Reasonable Chapters on ecological Foolishness - Librová, Hana (Masaryk University Monographs, 2021)
This book follows the successful titles "The Colourful and the Green: Chapters on Voluntary Simplicity" and "The Half-Hearted and the Hesitant: Chapters on Ecological Luxury." The author poses the question of why, at a time of continuing devastation of nature, people's interest in nature conservation has been decreasing. Are the media to blame or is our numbness toward ecological problems rooted in our mental makeup that tends to supress unpleasant realities? The author also wants to find out why some people have remained faithful to nature. To get to the answers, she applies sociological, philosophical, psychological, and theological perspectives. An unexpected question that may surprise some readers then becomes: Actually, why should we protect nature when it can take care of itself? It is not weak; it is strong and cruel. Librová's students Vojtěch Pelikán, Lucie Galčanová, and Lukáš Kala interview the children of "the Colourful," too: have they inherited their parents' modest lifestyle?